The Lurking Threats Of Communicable Diseases – Where Do We Stand - Zawwar Reza; Abdul Ahad Sohail; Syed Ali Fahad Kazmi (Pakistan Journal of Medicine and Dentistry, 2024)
As professionals in the healthcare industry, there is a duty deeply ingrained within us to be better today than what we were yesterday. This means that each day we have the opportunity to rise up to bigger challenges, whether it is to pass an Endotracheal tube into an unconscious patient with severe neck edema, or to increase the vaccine coverage to more rural areas. Understandably it is the decisions made at a national level which have the potential to be more impactful…